Think Perl 6 : how to think like a computer scientist - Rosenfeld, Laurent; Downey, Allen B. (O'Reilly Media, 2017)
If you want to learn how to program and think like a computer scientist, this practical guide will get you started on your programming journey with Perl 6, the new version of the popular programming language. Ideal for beginners, Think Perl 6 contains numerous exercises with multiple solutions and a lot of code examples.